Pregled zgodovine, poskus ukinitve in ponovno rojstvo slovensko-ameriške Župnije sv. Jožefa v Jolietu v zvezni državi Illinois - Herle, Dominik (Edinost in dialog, 2025)
The article discusses the history of the Slovenian-American Parish of St. Joseph in Joliet, Illinois, focusing on the attempt to close it in 2024 and the successful struggle of the parishioners to preserve it. St. Joseph Parish was founded in 1891 to meet the needs of the growing Slovenian community for religious services in their native language. Throughout its history, it has played an important role in the lives of Slovenian Immigrants and their descendants, providing them with spiritual care, education while also serving as a place to gather. In 2024, Bishop Ronald Aldon Hicks of Joliet decided to close the parish and merge it with other parishes in the diocese. He justified his decision on the grounds of a declining number of parishioners, financial difficulties and a shortage of priests. The parishioners of St. Joseph strongly opposed the Bishop's decision. They believed that the Bishop's claims were inaccurate and that the parish still played an important role in the life of the Slovenian-American community. They lodged an appeal with the Dicastery for the Clergy at the Vatican, refuting all of the Bishop's arguments. On 20 August 2024, the Dicastery granted the parishioners' request and annulled the Bishop's decree. This was a great victory for St. Joseph Parish and the Slovenian-American community in Joliet. This case study highlights the importance of ethnic parishes as centres of religious, cultural and social life for immigrant communities.
Keywords: ethnic identity; etnična identiteta; immigrant community; politično krščanstvo; priseljenska skupnost; Slovenian Americans; slovenski Američani; St. Joseph Parish in Joliet; United States of America; Združene države Amerike; župnija sv. Jožefa v Jolietu